DETERMINANTS OF INCOME AND WELFARE OF FISHERMEN IN DESA ADAT JIMBARAN, BADUNG REGENCY - Kadek Surya Astawa Putra; Made Kembar Sri Budhi (Adisam Publisher, 2025)
The welfare of fishermen in Desa Adat Jimbaran, Badung Regency, remains relatively low due to various interrelated factors, including limited human resources, the continued use of traditional fishing methods, restricted access to capital, poor financial management habits, and the underutilization of modern fishing technology. This study aims to analyze the determinants of fishermen’s income and welfare by focusing on three main variables: working capital, technology, and work experience. Using a quantitative approach with Partial Least Squares (PLS) as the analytical tool, this research was conducted among fishermen in Desa Adat Jimbaran, who face uncertainties in daily catch volumes and income. The findings reveal that working capital and work experience have a positive and significant effect on both income and welfare, while technology has a positive but statistically insignificant effect. Income is also found to be a significant mediating variable between the independent variables and fishermen’s welfare. These results suggest that while capital and experience are essential in enhancing income and living standards, the application of fishing technology has not produced optimal outcomes due to limited skills and high operational costs. Therefore, there is a need for training and improved access to user-friendly technology to strengthen the economic resilience of traditional fishing communities.